Implementation of The Merdeka Curriculum at Darul Mursyid Islamic Senior High School - Siregar, Hendra Irwandi; Hasibuan, Kholidah Hannum (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
Darul Mursyid Islamic Senior High School (Madrasah Aliyah Darul Mursyid) is an Islamic educational institution that plays a significant role in shaping the educational landscape for students at the secondary level. Understanding the current curriculum implementation practices—including teaching methods, assessment systems, and educational outcomes—is essential for evaluating their effectiveness and identifying areas for improvement. The curriculum is a vital component of the education system, serving as a guideline for the teaching and learning process. In madrasahs, the curriculum not only includes academic content but also emphasizes the inculcation of religious and moral values. This article aims to analyze the implementation of the curriculum at the school and the challenges encountered. The teaching methods at Madrasah Aliyah Darul Mursyid are likely influenced by traditional Islamic educational practices, which emphasize the study of religious texts such as the Qur’an and Hadith. This is a common characteristic of the madrasah-style education system, which focuses on traditional Islamic sciences. The assessment system in Islamic educational institutions like Madrasah Aliyah often includes both formative and summative assessments. These assessments are designed to evaluate students’ understanding of both religious and secular subjects. The integration of contextual teaching and learning approaches, as observed in other madrasah environments, can also be applied to enhance science learning outcomes. The success of curriculum implementation can be measured by students' ability to apply their knowledge in real-world contexts and their readiness for higher education or vocational activities. The purpose of this study is to identify and gather information regarding the implementation of the Merdeka Curriculum at Darul Mursyid Islamic Senior High School.